3-Layer Immunoperoxidase Protocol Reaction, Endomucin, and Alpha-smooth Muscle Actin Detection - Rukaia Sheneeb; Fawzia Takala (Khalij-Libya Journal of Dental and Medical Research, 2022)
Background and objectives. Immunohistochemistry (IHC) is the detection of antigens in tissue sections by specific antibodies. It has the unique advantage over other methods for detection proteins like α-Smooth Muscle Actin and endomucin, enabling the correlation of antigens with their location within a tissue. The aim of the study was to identify α-SMA and endomucin in cardiac muscle tissue and arterial blood vessels which have important diagnostic purposes. Methods. Three Specimens (aSMA, Endomucin and control) of formalin-fixed paraffin embedded mouse embryo tissue sections have been de-waxed, rehydrated. Then they were covered with accurate primary antibody: αSMA slide in dilute mouse monoclonal anti-smooth muscle actin, Endomucin slide in dilute rat monoclonal anti-endomucin and the control slide gets just PBS (no-primary control). Then the sections were covered with the right secondary antibody: αSMA slide with biotinylated rabbit anti-mouse IgGIgG diluted and Endomucin slide with biotinylated rabbit anti-rat IgG, control slide with either antibody. Next color reagent was applied; it contains 3,3′-Diaminobenzidine and 0.3% hydrogen peroxide. Finally examine slides using a microscope. Results. The results showed that there was different brown 3,3′-Diaminobenzidine staining patterns in the two test slides for the individual primary antibodies. The 3,3′-Diaminobenzidine Staining was highly expressed in the external part of the section as a result of the presence of α-Smooth Muscle Actin. Whereas, in case of Endomucin, the stain is expressed in the central part of specimens due to presence of the endothelial tissue. and no staining in the primary control sections. Conclusion. As a result of the presence of α-Smooth Muscle Actin in the muscular tissue,3,3′-Diaminobenzidine Staining was highly expressed in the external part of the section. However, in case of Endomucin the stain is expressed in the central part of specimens due to presence of the endothelial tissue.